Raeder syndrome: MR appearance. - Castillo, M; Kramer, L (American Journal of Neuroradiology, 1992)
A 40-year-old woman presented with symptoms compatible with Raeder syndrome. MR demonstrated narrowing of the left cavernous carotid artery. The high cervical portion of the left internal carotid artery was not identified. Angiography confirmed the narrowing of the cavernous carotid artery and showed marked and irregular stenosis of the distal cervical internal carotid artery. Involvement of the left sympathetic plexus and of ipsilateral cavernous sinus arteries is believed to have been the cause of the Raeder syndrome in this patient.